THE IMPORTANCE OF DISCOURSE IN THE PROCESS OF TEACHING ENGLISH - Aliyeva Gulnoza Olimjonovna Samarkand State Institute of Foreign Languages Samarkand, Uzbekistan (SCIENCE AND INNOVATION IDEAS IN MODERN EDUCATION, 2024)
The article is devoted to the consideration of the concept of “discourse.” The paper analyzes the main characteristics and types of discourse, defines the specifics of discourse competence, and emphasizes its importance in the process of teaching foreign language communication in the context of the new paradigm of Russian education. The author clarifies the definition of discourse and its main characteristics from the standpoint of the methodology of teaching foreign languages. Keywords: discourse; teaching a foreign language; communicative situation; bipolarity; motivation; characteristics of discourse; meta-meaning